Post-pandemic era: global trends, benefits, and barriers in integrating artificial intelligence into public health education - Akingbola, Adewunmi; Adegbesan, Abiodun; Tundealao, Samuel; Benson, Akpevwe Emmanuella; Makinde, Abdulfatai Olumide; Shekoni, Mayowa; Animashaun, Khalid; Fakiyesi, Tosin (Frontiers in Public Health, 2025)
The COVID-19 pandemic posed an unprecedented challenge to public health systems globally, with African countries exhibiting a wide range of outcomes in terms of preparedness, response, and resilience. This review explores the public health strategies deployed across the African continent during the pandemic, highlighting key successes, identifying critical failures, and synthesizing lessons to inform future health emergency preparedness. Drawing on existing literature, policy documents, and epidemiological data, the study examines the roles of leadership, community engagement, health communication, diagnostic capacity, and vaccine deployment. While several African countries successfully leveraged past epidemic experience, decentralized health systems, and innovative communication strategies, others struggled with misinformation, weak surveillance, and limited critical care infrastructure. The review also discusses the role of international collaboration, local innovation, and donor dependence in shaping response outcomes. Lessons from Africa’s handling of COVID-19 underline the importance of strengthening public health infrastructure, investing in health workforce development, improving health information systems, and ensuring equitable access to vaccines and therapeutics. This paper contributes to the growing discourse on pandemic preparedness and highlights Africa’s potential not only as a site of vulnerability but also of resilience and innovation in global public health.